Septic paravertebral abscess and inferior vena cava thrombosis complicated by uro-sepsis: Case report - Ibrahim Abdulghafoor Ibrahim Agha; Moamer Abdulghafoor Ibrahim; Yasser Thamer Salim; Khalid Waleed Ibrahim; Omar Mohsin Mohammed; Safaa Jassim Mohammed (Romanian Journal of Neurology)
Paravertebral abscess is an uncommon and potentially dangerous illness characterized by the buildup of pus in the anatomical area surrounding the spinal column. A 65-year-old female, who has diabetes and high blood pressure, came in with intense discomfort in her lower back that spreads to her lower limbs, making it difficult for her to move. She also has a high fever, excessive sweating, and has lost a large amount of weight. The blood tests indicate the following abnormalities: low Hb level of 9.6 g/dl, low MCV of 70 fl, elevated total white blood cell count of 15.8 × 109/L, elevated neutrophil count of 12.4 × 109/L, normal lymphocyte count of 2.8 × 109/L, high platelet count of 485 × 109/L, and elevated ESR of 110 mm/hr. The level of phosphatase was raised to 247 U/L, which is beyond the usual range of 40-150 U/L. The blood film reveals the presence of hypochromic microcytic red blood cells, which are indicative of iron deficiency anemia. There is also evidence of neutrophil leukocytosis in the white blood cells, with no immature cells observed. Additionally, an increase in platelets is observed in the film. The D-dimer level is 2009 ng/ml, which is within the normal range of less than 500 ng/ml. The CRP level is 48 gm/l, which is above the usual range of less than 6 gm/l. The bone marrow testing yielded normal results. The blood culture indicated the presence of Streptococcus epidermidis growth. Radiological tests revealed that a CE-MRI of the dorsal and lumbar spine indicated the presence of a para-aortic abscess together with septic thrombosis of the inferior vena cava. Paravertebral abscess is a critical emergent condition required a necessary therapy protocols to stabilize the patient status. The timing of intervention is crucial in cases of paravertebral abscess, as the existence of a mass can led to spinal cord compression.